Incidence of Corporate Income Tax (CIT) Exemption - Stanislas Agossadou (TIJAB (The International Journal of Applied Business), 2025)
Background: Tax incentives are widely used among developed and developing economies to promote and attract economic activity in their jurisdictions and can be introduced for a range of reasons (OECD, 2022). However, "those who pay tax do not necessarily bear the cost” (Martin & Mayneris, 2022). Similarly, the government that grants a tax exemption does not necessarily bear the cost of this tax exemption. Based on this point, the main question of this research is: what is the incidence of corporate income tax (CIT) exemption?Objective: This paper focuses on tax incidence, looking for the "real" loser or winner of corporate income tax (CIT) exemption.Method: The paper applies both tabular or graphical methods of analysis and fixed-effects panel models. An initial sample of two hypothetical identical firms is used. A second sample of 20 indebted firms with taxable earnings in France is used for the period from 2017 to 2021. The hypothesis of non-gratuity of cost and revenue is used.Results: We find that, in reality, corporate income tax (CIT) exemption results in the firm subject to CIT being the "real" loser and the firm exempt from CIT being the "real" winner; the tax incidence cancels out at government level.Conclusion: Any tax incentive on investment, financing or company profits is simply a diversion of profits from the company not eligible for the tax incentive to the company eligible for the tax incentive, the two companies being identical and belonging to the same class of financial and operating risk.